Self-Management Education for the Quality of Life of Patients with Pulmonary Tuberculosis - Eppy Setiyowati; Umi Hanik; Ni Njoman Juliasih; Achmad Wahdi (Journal for Quality in Public Health, 2020)
Introduction: Treatment for pulmonary tuberculosis (TB) may become a problem when the patients show no adherence to the treatment and feel bored with its long duration. This condition may lead to the drop out in the treatment. Therefore, this study aimed at analyzing the effects of self-management education on the quality of life of patients with pulmonary TB. Method: The design of this study is quasi-experiment conducted in 3 Puskesmas (Community Health Center), in which 150 respondents was divided into 2 groups: 75 respondents in the control group and 75 respondents in the treatment group. They were chosen as the samples by using simple random sampling technique. The data were collected by conducting pretest to measure the quality of life, doing intervention through self-management education, and finally providing posttest. Furthermore, the data were analyzed by using Mann Whitney U test and Wilcoxon signed rank test.Result: Change in perceptions that this disease is infected by Mycobacterium tuberculosis, the right place for the treatment is Puskesmas or hospitals, and a high hope for the cure needs supports form the family and medical workers Conclusion, self-management education increases the quality of life of the patients with pulmonary TB. The future research is expected to analyze their life expectancy more deeply.